Response to azacitidine in patients with chronic myelomonocytic leukemia according to overlap myelodysplastic/myeloproliferative neoplasms criteria. (May 2022) - Triguero, A.; Xicoy, B.; Zamora, L.; Jiménez, MJ.; García, O.; Calabuig, M.; Díaz-Beyá, M.; Arzuaga, J.; Ramos, F.; Medina, A.; Bernal, T.; Talarn, C.; et al.
Abstract: Background: Azacitidine (AZA) is approved for the treatment of high-risk chronic myelomonocytic leukemia (CMML) of myelodysplastic (MD) subtype. Data of response rates using the specific response criteria for this disease are scarce. The aim of this study was to evaluate the response to AZA in patients diagnosed with CMML from the Spanish Registry of Myelodysplastic Syndromes (MDS) applying the overlap myelodysplastic/myeloproliferative neoplasms (MDS/MPN) response criteria. Methods: We retrospectively studied 91 patients with CMML treated with at least one cycle of AZA from the Spanish Registry of MDS. As it was a real-world study, the response rate was evaluated between cycle 4 and 6, applying the MDS/MPN response criteria Findings: The overall response rate at cycle 4–6 was 58%. Almost half of the patients achieved transfusion independence and one quarter showed clinical benefit, regardless of the CMML French-American-British (FAB) and World Health Organization (WHO) subtypes and CMML Specific Prognosis Scoring (CPSS) risk groups. Toxicity was higher in the MD-CMML subtype. Interpretation: In our series, most CMML patients achieved an overall response rate with AZA according to the overlap-MDS/MPN response criteria regardless of the CMML FAB and WHO subtypes and CPSS risk groups. Thus, AZA may also be a treatment option for patients with the myeloproliferative CMML subtype and those with a lower-risk CPSS, but symptomatic. Highlights: Chronicmyelomonocytic leukemia patients treated with azacitidine achieve a highoverall response rate. Myeloproliferativechronic myelomonocytic leukemia could also benefit of treatment with azacitidine, as the myelodysplastic subtype. Myelodysplastic/myeloproliferativeresponse criteria also allow to analyze the clinical benefit to azacitidine inchronic myelomonocytic leukemia patients.